Phexpo: a package for bidirectional enrichment analysis of phenotypes and chemicals. Issue 2 (6th July 2020) - Hawthorne, Christopher; Simpson, David A; Devereux, Barry; López-Campos, Guillermo
Abstract: Phenotypes are the result of the complex interplay between environmental and genetic factors. To better understand the interactions between chemical compounds and human phenotypes, and further exposome research we have developed "phexpo, " a tool to perform and explore bidirectional chemical and phenotype interactions using enrichment analyses. Phexpo utilizes gene annotations from 2 curated public repositories, the Comparative Toxicogenomics Database and the Human Phenotype Ontology. We have applied phexpo in 3 case studies linking: (1) individual chemicals (a drug, warfarin, and an industrial chemical, chloroform) with phenotypes, (2) individual phenotypes (left ventricular dysfunction) with chemicals, and (3) multiple phenotypes (covering polycystic ovary syndrome) with chemicals. The results of these analyses demonstrated successful identification of relevant chemicals or phenotypes supported by bibliographic references. The phexpo R package (https://github.com/GHLCLab/phexpo ) provides a new bidirectional analyses approach covering relationships from chemicals to phenotypes and from phenotypes to chemicals.